TWO BASIC PRINCIPLES AND ITS TRANSLATION FOUND IN “I NYOMAN JATER” STORY - Dewa Made Agustawan; I Gede Angga Supriana; I Putu Eka Suardana (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2024)
This research focuses on the basic principle and their translation into Indonesian found in “I Nyoman Jater Story”. The aim of this research is to describe which orientation is more emphasized by the translator to translate Balinese language text into English language. Descriptive qualitative method was used in this research in order to explore the data of Balinese folklore entitled I Nyoman Jater. In analyzing the data, this research used the theory of translation that proposed by Newmark (1988) in order to know what types of emphasis implemented in this translation. The result of this research showed that most of the data of the translator emphasized target language in this translation. Those are 11 data as adaptation, 4 data as literal, and 3 data as communicative. So, in this translation the principle that emphasized here is target language